The effects of crowds on professional european basketball teams - Jiménez, J. L.; Valido, J.; Jiménez, M. (Journal of Sports Economics, 2025)
Do crowds affect professional basketball teams` performance? Using results from matches played in the EuroLeague, EuroCup, and ACB (Spain) before, during, and after the COVID period (2014-2024) allows us to answer this question. Our estimations conclude that the probability of a team winning at home is 5.6% lower in the absence of a home crowd in ACB and 5.76% in the case of EuroLeague. Moreover, the difference between home points and away points is lower and the percentage home fouls versus away fouls is higher, but both results are only significant for ACB. Finally, the absence of spectators in the stands does not affect shooting percentages.